Primary pigmented nodular adrenocortical disease (PPNAD) as an underlying cause of symptoms in a patient presenting with hirsutism and secondary amenorrhea: case report and literature review. (2nd December 2018) - Cyranska-Chyrek, Ewa; Filipowicz, Dorota; Szczepanek-Parulska, Ewelina; Nowaczyk, Marta; Ambroziak, Urszula; Toutounchi, Sadegh; Koperski, Łukasz; Bednarczuk, Tomasz; Meczekalski, Blazej; Ruchała, Marek
Abstract: Hypercortisolemia in females may lead to menstrual cycle disturbances, infertility, hirsutism and acne. Herewith, we present a 18-year-old patient, who was diagnosed due to weight gain, secondary amenorrhea, slowly progressing hirsutism, acne and hot flashes. Thorough diagnostics lead to a conclusion, that the symptoms was the first manifestation of primary pigmented nodular adrenocortical disease (PPNAD). All symptoms of Cushing syndrome including hirsutism and menstrual disturbances resolved after bilateral adrenalectomy. Our report indicates that oligo- or amenorrhea, hirsutism, acne in combination with weight gain, growth failure, hypertension and slightly expressed cushingoid features in a young woman requires diagnostics towards hypercortisolemia. Despite PPNAD is a very rare cause of ACTH-independent Cushing syndrome, it has to be taken into consideration, especially when adrenal glands appear to be normal on imaging and paradoxical rise in cortisol level in high-dose dexamethasone test is observed. Unlike in our patient, in vast majority of patients, PPNAD is associated with Carney complex (CC). Therefore, these patients and their first-degree relatives should be always carefully screened for symptoms of PPNAD, CC and genetic mutations of PRKAR1A, PDE11A, and PDE8B genes. 摘要: 女性高皮质醇血症可能导致月经周期紊乱、不孕、多毛症和痤疮。 在此, 我们报告一位18岁的病人, 因体重增加、继发性闭经、缓慢进展的多毛症、痤疮和潮热而被诊断为高皮质醇血症。我们由此得出结论, 这些症状是原发性色素结节性肾上腺皮质疾病（PPNAD）的首要表现。 库欣综合征的所有症状, 包括多毛症和月经紊乱在双侧肾上腺切除术后得到改善。我们的报告提示, 年轻女性出现少经或闭经、多毛症、痤疮、体重增加、生长停止、高血压和轻微的库欣样特征, 需要考虑高皮质醇血症的诊断。尽管PPNAD是ACTH非依赖性库欣综合征的非常少见的原因, 但必须加以考虑, 特别是当肾上腺在影像学上看起来正常时, 以及在大剂量地塞米松试验中观察到皮质醇水平反常升高时。与我们的患者不同, PPNAD绝大多数患者, 与Carney综合征（CC)）相关。因此, 这些患者及其一级亲属应始终仔细筛查PPNAD和CC的症状, 以及PRKAR1A、PDE11A和PDE8B这些基因的突变。